2007
DOI: 10.1196/annals.1396.028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Influences on Cognitive Function with Aging

Abstract: Human epidemiologic studies provide convincing evidence that dietary patterns practiced during adulthood are important contributors to age-related cognitive decline and dementia risk. Diets high in fat, especially trans and saturated fats, adversely affect cognition, while those high in fruits, vegetables, cereals, and fish are associated with better cognitive function and lower risk of dementia. While the precise physiologic mechanisms underlying these dietary influences are not completely understood, modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 67 publications
2
50
0
2
Order By: Relevance
“…2). In the last 3 decades, numerous studies suggested that modifiable lifestyle factors including a low-calorie diet (caloric restriction, CR), and specific micro-and macronutrients like unsaturated fatty acids (UFA), might exert beneficial effects on the aging brain (3)(4)(5)(6)(7). In animal models of aging and neurodegenerative diseases, CR protected hippocampal, striatal, and cortical neurons, and ameliorated functional decline (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…2). In the last 3 decades, numerous studies suggested that modifiable lifestyle factors including a low-calorie diet (caloric restriction, CR), and specific micro-and macronutrients like unsaturated fatty acids (UFA), might exert beneficial effects on the aging brain (3)(4)(5)(6)(7). In animal models of aging and neurodegenerative diseases, CR protected hippocampal, striatal, and cortical neurons, and ameliorated functional decline (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Nutrition also influences cognition, with both long term dietary patterns and the acute consumption of individual nutrients playing a role (Parrott and Greenwood 2007). For example, following an overnight fast, consuming a glucose-containing drink, compared with the ingestion of an artificially sweetened calorie-free placebo drink, is associated with transient cognitive benefits in older adults (Kaplan et al 2000;Riby et al 2004), with the most consistent enhancements reported in tests of verbal (Manning et al 1992(Manning et al , 1998Riby et al 2004) and non-verbal episodic memory (Allen et al 1996).…”
mentioning
confidence: 95%
“…Diet is an important lifestyle factor, which in recent times has been investigated for its influence on cognitive function and the incidence and onset of neurodegenerative disorders (1,2) . It has long been known that a diet high in saturated fats negatively impacts on cognitive processing and increases the risk of neurological dysfunction in both animals and human subjects (3,4) , while energy restriction (reduction in approximately 30 % energy intake) protects the brain from injury (5,6) .…”
Section: Flavonoids: Memory: Learning: Hippocampusmentioning
confidence: 99%